2018
DOI: 10.1016/j.amsu.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Independent predisposing factors for subcutaneous and deep wound collection after total thyroidectomy, a prospective cohort study

Abstract: BackgroundThe literature contains diverse and sometimes contradicting results about wound seroma following thyroidectomy. This is probably due to the subjective clinical estimation of seroma, or due to failure to differentiate between the occurrence of subcutaneous (SC) and deep wound collections. This work aimed at objectively investigating the factors affecting subcutaneous and deep wound seroma after thyroidectomy.MethodsThe relation between various operative and clinico-pathological factors and the collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Successful management of all complications with palliative care was reported which is similar to the literature worldwide. [15][16][17][18] Nevertheless, wound complications that likely occurred in the drained group in our study cannot be ignored, owing to the drain placement. Hence drains predispose wounds to the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Successful management of all complications with palliative care was reported which is similar to the literature worldwide. [15][16][17][18] Nevertheless, wound complications that likely occurred in the drained group in our study cannot be ignored, owing to the drain placement. Hence drains predispose wounds to the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, while hemostatic effects are well documented in other fields, its ability to reduce or prevent a seroma formation in the operative field remains controversial in thyroid surgery [ 5 6 ]. Regarding this issue, it has been reported that clinicopathologic factors, such as age, sex, body mass index (BMI) or dead space, the amount of fibrin glue used, and surgeon’s skill, may affect the outcome; therefore, the data on these factors should be collected to evaluate the actual impact of fibrin glue on the prevention of seroma after thyroidectomy [ 5 7 8 ].…”
Section: Introductionmentioning
confidence: 99%